(1231) الألعاب الإستراتيجية ومبدأ النهاية الصغرى للنهايات العظمى The Games Petition and the Principle of Liberal Endings in Grand Finals - مخلوف, إبراهيم أحمد (معهد التخطيط القومي, 2018)
ملخص تتناول هذه المذكرة البحثية التي أعدها الدكتور إبراهيم أحمد مخلوف عام ١٩٧٨ موضوع "الألعاب الاستراتيجية ومبدأ النهاية الصغرى للنهايات العظمى"، حيث تقدم ملخصاً لرسالة دكتوراه تستعرض نظرية الألعاب كأداة رياضية لاتخاذ القرارات في مواقف الصراع وتضارب المصالح. وتوضح الدراسة المبادئ الأساسية للنظرية التي وضعها "فون نيومان"، مع التركيز على مفهوم الاستراتيجية المثالية التي تضمن للاعب الحصول على أفضل نتيجة ممكنة بغض النظر عن تصرفات الخصم، وذلك من خلال تحليل الأشكال المختلفة للألعاب سواء كانت ذات معلومات تامة أو غير تامة، واستخدام أمثلة تطبيقية مثل لعبة "البوكر" لتوضيح أساليب الخديعة والشك والمناورة الرياضية. كما يستعرض الملف تطبيقات هذا المبدأ الرياضي في مجالات أوسع تشمل تفسير النماذج الاقتصادية المعقدة، مثل نموذج "نيومان" للنمو الاقتصادي، عبر تحويل اللعبة إلى برنامج خطي يسهل حله باستخدام الحاسب الإلكتروني. وتتعمق المذكرة في دراسة الألعاب العامة المكونة من أكثر من شخصين، مبرزةً أهمية التحالفات والتعويضات بين اللاعبين والدور الذي تلعبه "الدالة المميزة" في تحديد العوائد المتوقعة لكل تحالف، مما يلقي الضوء على كيفية استخدام هذه النظريات الرياضية لفهم وتوقع السلوك البشري والاقتصادي في المجتمع وتحقيق التوازن بين القوى المتصارعة institution/organization]. This research memorandum, prepared by Dr. Ibrahim Ahmed Makhlouf in 1978, addresses the topic of "Strategic Games and the Principle of the Least End of the Maximum Ends." It presents a summary of a doctoral dissertation that examines game theory as a mathematical tool for decision-making in situations of conflict and competing interests. The study clarifies the fundamental principles of the theory developed by von Neumann, focusing on the concept of the optimal strategy that guarantees the player the best possible outcome regardless of the opponent's actions. This is achieved through an analysis of different forms of games, whether with complete or incomplete information, and by using practical examples such as poker to illustrate the methods of deception, doubt, and tactical maneuvering . The document also explores the applications of this mathematical principle in broader fields, including the interpretation of complex economic models, such as Newman's model of economic growth, by transforming the game into a linear program that can be easily solved using a computer. The memo delves into the study of general games involving more than two people, highlighting the importance of alliances and compensations between players and the role of the "distinctive function" in determining the expected returns for each alliance. This sheds light on how these mathematical theories can be used to understand and predict human and economic behavior in society and to achieve a balance between conflicting forces .